An integrated composite structure with reduced electrode / bipolar plate contact resistance for vanadium redox flow battery. (15th March 2022) - Jeong, Kwang Il; Jeong, Jae-Moon; Oh, Jaehyung; Lim, Jun Woo; Kim, Seong Su
Abstract: Reducing the cell resistance is a major challenge in the development of vanadium redox flow batteries (VRFBs), which are operated by stacking several components such as electrodes, bipolar plates, and membranes. In particular, the contact resistance between the bipolar plates and electrodes needs to be minimized, as it can lead to a nonuniform charge distribution. The integration of electrodes and bipolar plates is an ultimate solution to remove the contact resistance. Conventional ways of integrating electrodes and bipolar plates are to electrically connect through adhesion using a conductive binder. However, in the conventional integration process, it is challenging to avoid the formation of new interfaces between the conductive binder and components. These new interfaces can restrict the substantial reduction in the contact resistance of the integrated structures. In this paper, we introduce a novel fabrication method to integrate electrodes and bipolar plates without contact resistance. The integrated structure was fabricated with a single sheet of graphite felt so that the electrode and bipolar plate could be interconnected with graphite fibers. Before the compression molding to fabricate the bipolar plate part, glucose was preimpregnated and cured to the electrode part to prevent a change in porosity owing to the compression of the graphite felt. In a VRFB single-cell test at a current density of 100 mA cm −2, the integrated structure had the highest system efficiency (73.16%), 3% higher than that of the conventional cell.